Influencia de la encina y el alcornoque sobre las variables físico-químicas del suelo y la regeneración del bosque - CORTÉS, A.; NAVARRO-CERRILLO, R. M.; ARA, M. A.; SÁNCHEZ, R.; GÓMEZ- APARICIO, L.; MARAÑON, T.; VILLAR, R. (VI Congreso Forestal Español, 2013)
El objetivo de este trabajo fue conocer el efecto o la “huella” de la vegetación arbórea sobre las características físico-químicas del suelo y la regeneración de dos especies de Quercus (Q. ilex, Q. suber). Para ello, se realizó un muestreo en dos parcelas de bosque mixto de encina y alcornoque en la Sierra de Córdoba (Trasierra). Las parcelas fueron de 60 x 60 m con una malla de 10 m, resultando 36 puntos de muestreo. En cada uno de los puntos de muestreo se tomaron muestras de suelo a dos profundidades (0-10 y 10-20 cm) y se analizaron las principales variables físico-químicas (textura, pH, N y C, disponibilidad de P, K, Ca y Mg). Además, en cada parcela se realizaron medidas de humedad del suelo y luz, así como la altura y el diámetro del tronco a 130 cm de todos los árboles de la parcela. Para evaluar el efecto del árbol sobre la regeneración, se sembraron semillas de encina y alcornoque y se midió la emergencia, el crecimiento y la supervivencia de las plántulas tras el primer verano. La influencia del árbol se midió en relación a la cantidad de desfronde caído a lo largo de un año. Los resultados mostraron un efecto del arbolado sobre variables físico-químicas del suelo. Así, en las zonas de mayor influencia la densidad aparente del suelo fue menor y la fertilidad del suelo mayor (mayor concentración de N, P, K y Ca). Sin embargo, a pesar de estos cambios en las características del suelo, no se encontró ninguna relación con la emergencia, el crecimiento o la supervivencia de plántulas tras el período estival. Aunque no es de descartar que en plantas de mayor edad, las características del suelo tengan una influencia significativa en el crecimiento y supervivencia, dado que durante el primer año, las plántulas de Quercus dependen fuertemente de las reservas de la semilla
The following values have no corresponding Zotero field: periodical: VI Congreso Forestal Español pub-location: Vitoria
Keywords: Alcornoque; encina; huella del árbol; nutrientes; Quercus; regeneración

Oak seedling survival and growth along resource gradients in Mediterranean forests: implications for regeneration in current and future environmental scenarios - Gómez-Aparicio, L.; PÉREZ-RAMOS, I. M.; Mendoza, I.; Matías, L.; Quero, J. L.; Castro, J.; Zamora, R.; MARAÑON, T. (Oikos, 2008)
Understanding seedling performance across resource gradients is crucial for defining the regeneration niche of plant species under current environmental conditions and for predicting potential changes under a global change scenario. A 2-year field experiment was conducted to determine how seedling survival and growth of two evergreen and two deciduous Quercus species vary along gradients of light and soil properties in two Mediterranean forests with contrasting soils and climatic conditions. Half the seedlings were subjected to an irrigation treatment during the first year to quantify the effects on performance of an alteration in the summer drought intensity. Linear and non-linear models were parameterized and compared to identify major resources controlling seedling performance. We found both site-specific and general patterns of regeneration. Strong site-specificity was found in the identity of the best predictors of seedling survival: survival decreased linearly with increasing light (i.e. increasing desiccation risk) in the drier site, whereas it decreased logistically with increasing spring soil water content (i.e. increasing waterlogging risk) in the wetter site. We found strong empirical support for multiple resource limitation at the drier site, the response to light being modulated by the availability of soil resources (water and P). Evidence for regeneration niche partitioning among Quercus species was only found at the wetter site. However, at both sites Quercus species shared the same response to summer drought alleviation through water addition: increased first-year survival but not final survival (i.e. after two years). This suggests that extremely dry summers (i.e. the second summer in the experiment) can cancel out the positive effects of previous wetter summers. Therefore, an increase in the intensity and frequency of summer drought with climate change might cause a double negative impact on Quercus regeneration, due to a general reduction in survival probability and the annulment of the positive effects of (infrequent) ‘wet’ years. Overall, results presented in this study are a major step towards the development of a mechanistic model of Mediterranean forest dynamics that incorporates the idiosyncrasies and generalities of tree regeneration in these systems, and that allow simulation and prediction of the ecological consequences of resource level alterations due to global change.
Keywords: abiotic factors; growth (voyant); light; Mediterranean forests; Quercus; Regeneration; seedling survival; soil conditions; summer drought